TINDAK KEKERASAN DALAM RUMAH TANGGA (STUDI TENTANG KEKERASAN PADA MASYARAKAT PERKEBUNAN DI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU) - Siti Miswatun; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study was conducted on people who committed domestic violence in plantation communities. The purpose of this study was to analyze the factors behind the domestic violence in the plantation community. The focus of this research is the life profile of plantation community in Seberida Sub-district, Indragiri Hulu Regency. Sampling technique in this study is Purposive Sampling and menetapka number of samples of 7 people. Researchers use qualitative research methods and Instruments data are observations, interview guides, and documentation. According to the research, it can be concluded that the profile of domestic violence acts as a palm oil plantation. The subject of this research can be said that violence in the household can be caused by economic factors that can not fulfill their life and pressure either individual self or from society society and can not solve household problems kinsely so that can trigger violence act. Behavior is a behavior that is not in accordance with the values and norms in society. Then a patriarchal theory in which people consider men to be more powerful than women. So that belief can trigger domestic violence because men are more powerful than women. Men are also heads of families who earn a living for families, so women do not dare to fight when men do violence. Women also consider domestic violence a family disgrace, so women do not dare to tell or report the incident to the authorities. Keywords: Violence, Plantation Society